Hallowe'en at Merryvale - Burnett, Alice Hale; Lester, Charles F. (Salt Lake City, UT : Project Gutenberg, 2005)
"Hallowe'en at Merryvale" by Alice Hale Burnett is a children's book written in the early 20th century. This charming story focuses on the joyous Halloween festivities experienced by a group of young boys in the small town of Merryvale. It is a delightful portrayal of childhood, adventure, and the traditions surrounding Halloween, capturing the spirit of camaraderie among the boys as they participate in various fun games and activities. In the story, the main character, Thomas Brown, known as Toad, prepares for a Hallowe'en party at his home, eagerly inviting all his friends. The night unfolds with a series of festive games, such as apple swinging, fortune telling by a witch, and searching for a silver coin in flour. Each game is filled with excitement and laughter, showcasing themes of friendship and adventure. The boys also enjoy delicious treats and the customary birthday cake, as Toad$1 (Bs birthday coincides with Halloween. The narrative culminates in joyful interactions, playful challenges, and light-hearted mischief, effectively encapsulating the innocence and exuberance of childhood. (This is an automatically generated summary.)s
Release date is 2005-11-23
E-text prepared by Suzanne Shell, Emmy, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Halloween -- Juvenile fiction